Research progress on female reproductive toxicity of bisphenols - Jia PENG; Xiangzhu YAN; Jiasi LIU; Xiaopeng ZHONG; Simin YAO; Yiyan MA; Shuhua TAN (环境与职业医学)
Bisphenols (BPs) are extensively used in food packaging, personal care products, and plastics, making them prevalent in both living and working environments, which has raised significant concern. As endocrine-disrupting chemicals, BPs exert toxic effects on the female reproductive system by binding to estrogen receptors, thereby activating or inhibiting the expression of genes related to reproductive functions, which disrupts the normal function of the endocrine system. This paper reviewed the effects of bisphenol A (BPA), bisphenol S (BPS), and bisphenol F (BPF) on female reproductive function, focusing on three key aspects: the effects on the female reproductive organs, the occurrence of associated reproductive disorders, and the mechanisms of toxicity. Specifically, this review highlighted the effects on ovarian function, uterine morphology and function, and fallopian tube function, as well as their correlation with polycystic ovary syndrome, endometriosis, miscarriage, and eclampsia. Additionally, the toxic mechanisms of BPs exposure were summarized, providing a scientific basis for future research on the impact of BPs on the female reproductive system, as well as for the assessment of potential health risks and the development of preventive measures.